2020
DOI: 10.1590/0102-311x00215319
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease due to microcephaly associated with the Zika virus in Colombia

Abstract: In 2015, the Zika virus was introduced in Colombia. The emergence of this arbovirus is a public health challenge for the country, considering the association between the infection and congenital disorders such as microcephaly. Thus, we estimated the burden of disease due to microcephaly associated with Zika in Colombia and its administrative subdivisions for the period 2015-2016. We conducted an exploratory ecological study, using as unit of measurement disability-adjusted life years (DALYs). The cases of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…No specific studies for the burden of disease by CZS were found in the literature, but there were two studies on microcephaly associated with ZIKV 12 , 19 . More-Salamanca et al 19 , estimated 9.48 DALYs lost for each case of microcephaly associated with Zika virus in Colombia from 2015 to 2016, a value that is higher than that estimated in this study, which was 8.36 DALYs lost for each case from 2015 to 2020. When considering the period from 2015 to 2016, our analysis reveals that the estimated DALYs lost in Brazil are lower than the number of DALYs lost in Colombia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No specific studies for the burden of disease by CZS were found in the literature, but there were two studies on microcephaly associated with ZIKV 12 , 19 . More-Salamanca et al 19 , estimated 9.48 DALYs lost for each case of microcephaly associated with Zika virus in Colombia from 2015 to 2016, a value that is higher than that estimated in this study, which was 8.36 DALYs lost for each case from 2015 to 2020. When considering the period from 2015 to 2016, our analysis reveals that the estimated DALYs lost in Brazil are lower than the number of DALYs lost in Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…Up to the time at which this study was carried out, the value of weight/burden of disability for CZS and the duration of the disease had not been described in the literature. For this reason, we used the value adopted by Mora-Salamanca et al 19 for calculating this metric when estimating the DALYs for ZIKV-associated microcephaly in Colombia, which is 0.16. This value was described by Salomon et al 20 and Alfaro-Murillo et al 12 and refers to the disability weight for severe intellectual disability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Colombia, a record number of microcephaly cases per epidemiological week occurred during the Zika virus epidemic (29,30). Nationally, it was estimated that between 10 173.16 and 10 860.57 disability-adjusted life years (DALYs) were lost due to microcephaly caused by Zika-virus (31).…”
Section: Zika Virusmentioning
confidence: 99%
“…El SGB es una entidad importante para el obstetra ya que el embarazo puede estar asociado a su aparición, además de estar asociado al virus del zika, infección viral que afectó a nuestra región en una epidemia en 2015 y 2016 17 , con especial repercusión en la salud perinatal 18 . Por tanto, el obstetra debe pensar en esta entidad y sus diferentes variantes que incluyen el SMF, ya que su manejo en la gestante puede requerir un equipo interdisciplinario.…”
Section: Introductionunclassified